Prospective associations of age at complementary feeding and exclusive breastfeeding duration with body mass index at 5–6 years within different risk groups. Issue 8 (25th April 2018) - Sirkka, O.; Vrijkotte, T.; Halberstadt, J.; Abrahamse‐Berkeveld, M.; Hoekstra, T.; Seidell, J.; Olthof, M.
Summary: Background: Children with overweight or obesity are at risk for developing obesity in adulthood. Certain maternal characteristics, such as ethnicity, education, body mass index (BMI) or neighbourhood, are determinants for childhood overweight risk. There are large variations in how mothers differing in these characteristics feed their infants. Therefore, associations of age at complementary feeding, exclusive breast feeding duration with childhood overweight may differ in these groups. Understanding these associations would be essential to develop overweight prevention strategies. Objectives: The objective of this study is to study the associations of age at complementary feeding, exclusive breastfeeding duration with BMI‐standard deviation score (SDS) at 5–6 years within risk groups. Methods: Using data from the Amsterdam Born Children and their Development study, a population‐based birth cohort ( n  = 4495), we formed groups of children at varying risk of overweight according to maternal characteristics of ethnicity, education, pre‐pregnancy BMI and neighbourhood. Linear and logistic regression analyses were conducted. Results: Complementary feeding after 5 months of age was associated with lower BMI‐SDS in children of mothers of Dutch ethnicity (B: −0.12; 95% CI: −0.21, −0.04), medium‐level education (−0.19; −0.30, −0.08), normal BMI (−0.08; −0.16, −0.01) and high‐risk neighbourhood (−0.16; −0.29, −0.02). Compared with exclusive breastfeeding for <3 months, exclusive breastfeeding for ≥6 months was associated with lower BMI‐SDS in groups of medium‐level education (−0.28; 0.44, −0.11), normal BMI (−0.18; −0.29, −0.08) and medium‐risk (−0.18; −0.33, −0.04) and high‐risk (−0.22; −0.42, −0.02) neighbourhoods. Conclusions: Associations between infant feeding practices and childhood BMI may differ between risk groups, implying that overweight prevention strategies should be group‐specific.